Propuesta de Aula Museo Pedagógica para fortalecer la educación patrimonial en los estudiantes del Colegio de Bachillerato Chambo - Saula Huaraca, Katy Belén (2022)
This research seeks to strengthen heritage education and the teaching-learning process of students of the Chambo High School through the "Proposal for a pedagogical classroom museum to strengthen the heritage education of students of the Chambo High School." During the pre-professional practices, it could be observed that the students showed low interest in the learning process in the History subject, based on this problem it was considered necessary to prepare this proposal, in order that the students feel motivated to learn since this proposal represents a didactic strategy that allows stimulating the teaching-learning process, in addition to relating theoretical concepts through concrete and tangible material and analyzing the level of influence they generate in today's society. To develop this work, it was necessary to apply qualitative research. We worked with non-numerical information obtained through interviews with different actors of the educational community, seeking to analyze the level of incidence of the problem evidenced and the feasibility of the proposal. It was generated to solve it. The method that was implemented was the inductive - deductive, through which conclusions could be generated based on specific aspects and elements of the daily reality of the educational institution and at the same time break down and identify features based on macro situations.